Advanced Disadvantage Factor Method for Homogenized Effective Cross Section Calculation in FCM fuel - YI Siyu;LIU Zhouyu;YIN Wen (Yuanzineng kexue jishu, 2022)
Conventional PWR fuel only needs to consider the single heterogeneity between fuel rods, but FCM fuel also needs to consider the double heterogeneity between particles and matrix. Disadvantage factor method is a typical method to solve double heterogeneity. But there are still some problems in this method. Firstly, the equivalent model for calculating the disadvantage factor is established by the conservation of volume weight, which introduces the assumption that the particles are uniformly distributed in the infinite matrix and cannot consider the macroscopic heterogeneity. Secondly, the disadvantage factor in the non-resonace energy region is obtained by ensuring the conservation of first flight collision probability in the 3D penetration model, but this method cannot meet the requirements of high-precision calculation in FCM fuel. To solve these problems, this paper proposes an improved disadvantage factor method based on the previous work. The improved disadvantage factor method mainly makes two improvements on the traditional method. Firstly, equivalent one-dimensional sphere model based on the Dancoff factor replaces the volume-weight equivalent model. Secondly, in the processing of non-resonance energy range, eigenvalue calculation is used in the new model to obtain multi-group disadvantage factors. This method was implemented in NECP-X and verified in different working conditions and problems of different scales. All the results are in good agreement with the reference solutions, which proves that the proposed method can effectively deal with the double heterogeneity in FCM fuel and obtain accurate effective multi-group cross sections.